Current Evidence and Future Directions of Berberine Intervention in Depression - Zhu, Wen-Qian; Wu, Hui-Ying; Sun, Zhi-Hui; Guo, Yi; Ge, Tong-Tong; Li, Bing-Jin; Li, Xin; Cui, Ran-Ji (Frontiers in Pharmacology, 2022)
A major type of serious mood disorder, depression is currently a widespread and easily overlooked psychological illness. With the low side-effects of natural products in the treatment of diseases becoming the pursuit of new antidepressants, natural Chinese medicine products have been paid more and more attention for their unique efficacy in improving depression. View from the current study, the positive antidepressant effects of berberine are encouraging. There are a lot of work needs to be done to accurately elucidate the efficacy and mechanism of berberine in depression. In this review, the relevant literature reports on the treatment of depression and anxiety by berberine are updated, and the potential pharmacological mechanism of berberine in relieving depression have also been discussed.